Incidental Cryptococcal lung mass in an immunocompetent patient. Issue 5 (3rd September 2019) - Lu, Michael; Raza, Rafi
ABSTRACT: Cryptococcus is an encapsulated fungal organism often implicated in central nervous system and pulmonary disease in patients with AIDS or other immunocompromising diseases. However, immunocompetent hosts can also be infected. In these cases, symptoms are generally mild and common radiographic findings include small, well-defined, smoothly marginated pulmonary nodules. We present a case of a 31-year-old man without any immunocompromising factors found to have pulmonary Cryptococcal infection presenting as a large lung mass.